2012
DOI: 10.1155/2012/501032
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of San-Huang-Xie-Xin-Tang in the MPP+/MPTP Models of Parkinson’s DiseaseIn VitroandIn Vivo

Abstract: San-Huang-Xie-Xin-Tang (SHXT), composed of Coptidis rhizoma, Scutellariae radix, and Rhei rhizoma, is a traditional Chinese medicine used for complementary and alternative therapy of cardiovascular and neurodegenerative diseases via its anti-inflammatory and antioxidative effects. The aim of this study is to investigate the protective effects of SHXT in the 1–methyl–4–phenylpyridinium (MPP+)/1–methyl–4–phenyl–1,2,3,6–tetrahydropyridine (MPTP) models of Parkinson's disease. Rat primary mesencephalic neurons and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Several authors have shown that ROS is closely associated with MPP + ‐induced neurotoxicity in PD and have suggested that antioxidative agents might be neuroprotective (Di Monte et al, ; Lee et al, ; Lo et al, ; Li et al, ). To investigate the antioxidative effects of morin, we evaluated ROS by measuring fluorescence intensities of DCF, an indicator of hydroxyl radical formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have shown that ROS is closely associated with MPP + ‐induced neurotoxicity in PD and have suggested that antioxidative agents might be neuroprotective (Di Monte et al, ; Lee et al, ; Lo et al, ; Li et al, ). To investigate the antioxidative effects of morin, we evaluated ROS by measuring fluorescence intensities of DCF, an indicator of hydroxyl radical formation.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have indicated that morin has antioxidant effects in models of excitotoxicity and experimental ischemia (Gottlieb et al, ) and that it is also effective in preventing and reversing Aβ destabilization (Lemkul and Bevan, ; Boopathi and Kolandaivel, ). In addition, several studies have indicated that ROS may be involved in MPP + ‐induced neurotoxicity (Di Monte et al, ; Lee et al, ; Lo et al, ; Li et al, ). In the present study, morin was shown to exert a neuroprotective effect against MPP + ‐induced cytotoxicity in primary neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Primary mesencephalic neuronal cultures were prepared from ventral mesencephalon dissected from 15-day-old embryos (E15) of pregnant Sprague-Dawley rats as previously described (Lo, Shih, Tseng, & Hsu, 2012;Tseng, Chang, & Lo, 2014). Animal handling was conducted in accordance with the National Institutes of Health (NIH) guidelines.…”
Section: Preparation Of Primary Mesencephalic Cell Cultures and Drumentioning
confidence: 99%
“…Various combinations of herbs have been used in traditional Chinese and Korean medicine for centuries, and recent research has suggested that some of these herbs may have neuroprotective effects in rat models of PD[ 60 ]. Anecdotal evidence shows that some of these herbs may offer beneficial effects in PD, although RCTs are needed to assess safety and efficacy.…”
Section: Resultsmentioning
confidence: 99%